2020
DOI: 10.1080/21691401.2020.1725024
|View full text |Cite|
|
Sign up to set email alerts
|

Long intergenic non-coding RNA 1939 eliminates proliferation and migration of human renal cell carcinoma (RCC) cells by down-regulation of miR-154

Abstract: Renal carcinoma (RCC) is widely accepted as a malignant tumour of urinary system. Long intergenic non-coding RNA 1939 (LINC01939) is a novel lncRNA which was found to be down-regulated in RCC. Thus, we set out to explore the effect and regulation mechanism of LINC01939 in RCC. LINC01939 and miR-154 in RCC tissues and cell lines were detected using qRT-PCR assay. To examine cellular viability of ACHN and CAKI-1 cells, cell counting kit-8 (CCK-8) assay was exploited here. Flow cytometric analysis was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Cell migration was evaluated via wound healing assay as reported previously 26 . Different concentrations of Sal‐A (0–50 µmol/L) were treated with NSCLC cells for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration was evaluated via wound healing assay as reported previously 26 . Different concentrations of Sal‐A (0–50 µmol/L) were treated with NSCLC cells for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Functionally, lncRNA NBAT1 functions as a ceRNA for miR-346 to upregulate GSK3β and mitigate cancer cell proliferation, invasion, and metastasis (Xue et al, 2019[ 64 ]). To further investigate the interplay between lncRNAs and miRNAs involved in RCC tumorigenesis, Zhang et al (2020[ 73 ]) reported that the long intergenic ncRNA 1939 (LINC01939) regulates tumor cell growth and progression through downregulating miR-154. The overexpression of LINC01939 inactivates Wnt/β-catenin pathway through suppressing miR-154 in RCC.…”
Section: The Interplay Between Ncrnas and Wnt/β-catenin Pathway In Ki...mentioning
confidence: 99%
“…Mechanically, LINC01939 attenuates cancer cell growth and metastasis by downregulating cyclin D1, MMP2, and MMP9. Moreover, LINC01939 was found to induce RCC cell apoptosis through inducing the expression of pro-apoptotic factors including bax and caspase-3 (Zhang et al, 2020[ 73 ]).…”
Section: The Interplay Between Ncrnas and Wnt/β-catenin Pathway In Ki...mentioning
confidence: 99%
“…The long intergenic non-coding RNA 1939 (LINC01939) is a novel lncRNA and was first confirmed to be downregulated in gastric cancer and involved in cancer progression 91 . Recently, the latest study indicated that LINC01939 possessed decreased expression in RCC tissues 92 . Upregulation of LINC01939 inhibited the proliferation and migration, as well as induced the apoptosis of ACHN and CAKI-1 cells by decreasing the level of miR-154 with the bluntness of Wnt/$ catenin and Notch 92 .…”
Section: Linc01939mentioning
confidence: 99%
“…Recently, the latest study indicated that LINC01939 possessed decreased expression in RCC tissues 92 . Upregulation of LINC01939 inhibited the proliferation and migration, as well as induced the apoptosis of ACHN and CAKI-1 cells by decreasing the level of miR-154 with the bluntness of Wnt/$ catenin and Notch 92 .…”
Section: Linc01939mentioning
confidence: 99%